2018
DOI: 10.1177/1934578x1801300603
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxicity of 28-N-Propargylaminoalkylated 2,3-Indolotriterpenic acids

Abstract: A new series of propargylaminoalkyl derivatives with N-methylpiperazine and morpholine fragments was obtained by modification of the carboxyl group of [3,2b]-indolotriterpenic acids (N-propargylation, Cu(I) catalyzed Mannich reaction). Cytotoxicity assays demonstrated that oleanane-type conjugate with N-methylpiperazine exhibited high antitumor activity against leukemia cell line SR and non-small cell lung cancer cell line NCI-H460.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The introduction of heterocyclic fragments, especially piperazine, has been demonstrated to enhance anticancer properties [ 31 ]. Recently we have found that modification of triterpenoids to indole derivatives on the A-ring with amidation to C28-amide, as well as the introduction of piperazine or N -methyl-piperazine, have a positive effect on anticancer activity [ 32 , 33 ]. Chalcone derivatives of messagenine and platanic acid [ 25 ], polyamino-lupanes [ 34 ], A-azepano-, and 3-amino-3,4-seco-triterpenoids [ 35 ] were also found to be effective antiproliferative agents against different cancer cell lines with submicromolar concentration values of GI 50 < 1 μM.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of heterocyclic fragments, especially piperazine, has been demonstrated to enhance anticancer properties [ 31 ]. Recently we have found that modification of triterpenoids to indole derivatives on the A-ring with amidation to C28-amide, as well as the introduction of piperazine or N -methyl-piperazine, have a positive effect on anticancer activity [ 32 , 33 ]. Chalcone derivatives of messagenine and platanic acid [ 25 ], polyamino-lupanes [ 34 ], A-azepano-, and 3-amino-3,4-seco-triterpenoids [ 35 ] were also found to be effective antiproliferative agents against different cancer cell lines with submicromolar concentration values of GI 50 < 1 μM.…”
Section: Introductionmentioning
confidence: 99%
“…reaction of C-28-propargyl amide or ester derivatives of 2,3-indolo-triterpenic acid possess the anticancer activity [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the last decade one of the priority topics in the chemistry of triterpenoids is the synthesis of various alkynyl derivatives with subsequent modification by click-chemistry to produce biologically active compounds bearing a 1,2,3-triazolyl fragment [14,15]. The conjugates obtained by click or Mannich reaction of C-28-propargyl amide or ester derivatives of 2,3-indolo-triterpenic acid possess the anticancer activity [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 2,3-indolouvaol (51) and 2,3-indolo-28-cyanoethoxybetulin (53) showed potential in vitro antitumor activity against NCI-H522 and COLO 205 cells, inducing the death of 12.65% and 42.78% of these cells, respectively [93]. Khusnutdinova et al [94] attempted the modification of the carboxyl group of [3,2b]indolotriterpenic acids (N-propargylation, Cu(I) catalyzed Mannich reaction) with Nmethylpiperazine and morpholine moiety. Among the modified compounds, oleananetype conjugate with N-methylpiperazine 56 (Figure 5) displayed the highest anticancer potency against leukemia cell line SR (−2.2%) and nonsmall cell lung cancer cell line NCI-H460 (−25.3%).…”
Section: Indolementioning
confidence: 99%
“…Khusnutdinova et al [ 94 ] attempted the modification of the carboxyl group of [3,2b]-indolotriterpenic acids (N-propargylation, Cu(I) catalyzed Mannich reaction) with N-methylpiperazine and morpholine moiety. Among the modified compounds, oleanane-type conjugate with N-methylpiperazine 56 ( Figure 5 ) displayed the highest anticancer potency against leukemia cell line SR (‒2.2%) and nonsmall cell lung cancer cell line NCI-H460 (‒25.3%).…”
Section: Indolementioning
confidence: 99%